2011
DOI: 10.1038/leu.2011.166
|View full text |Cite
|
Sign up to set email alerts
|

Eμ/miR-125b transgenic mice develop lethal B-cell malignancies

Abstract: MicroRNA-125b-1 (miR-125b-1) is a target of a chromosomal translocation t(11;14)(q24;q32) recurrently found in human B-cell precursor acute lymphoblastic leukemia (BCP-ALL). This translocation results in overexpression of miR-125b controlled by immunoglobulin heavy chain gene (IGH) regulatory elements. In addition, we found that six out of twenty-one BCP-ALL patients without t(11;14)(q24;q32) showed overexpression of miR-125b. Interestingly, four out of nine patients with BCR/ABL-positive BCP-ALL and one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 33 publications
3
68
0
3
Order By: Relevance
“…These observations are consistent with previous reports on the miR-99b;125a tricistron in the murine system (Guo et al 2010;Gerrits et al 2012). It was previously reported that miR-125a or miR-125b overexpression confers a competitive advantage to HSCs, leading to a gradual increase of chimerism in murine transplantation models (Guo et al 2010;Ooi et al 2010;Enomoto et al 2011). When g-retroviral vectors were used, which increased miR-125 expression level by 500-fold to several thousand-fold, development of myeloproliferative disease (MPD) and leukemia was observed (Gerrits et al 2012;for discussion, see O'Connell et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…These observations are consistent with previous reports on the miR-99b;125a tricistron in the murine system (Guo et al 2010;Gerrits et al 2012). It was previously reported that miR-125a or miR-125b overexpression confers a competitive advantage to HSCs, leading to a gradual increase of chimerism in murine transplantation models (Guo et al 2010;Ooi et al 2010;Enomoto et al 2011). When g-retroviral vectors were used, which increased miR-125 expression level by 500-fold to several thousand-fold, development of myeloproliferative disease (MPD) and leukemia was observed (Gerrits et al 2012;for discussion, see O'Connell et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, the expression of miR-125a/b is highly enriched in hematopoietic stem cells (20)(21)(22). Translocation and overexpression have been reported in acute myeloid leukemia and MPN patients (23)(24)(25). Overexpression of miR-125a or miR-125b greatly enhances the hematopoietic stem cell pool and output, and can induce MPN in mice (21,26).…”
Section: Functional Genomics Screen Identified Mir-125 Family Mirnas Asmentioning
confidence: 99%
“…Although leukemia is induced by overexpression of miR-125b in several models (21,24,(26)(27)(28), myeloproliferation could be the predominant effect of miR-125a overexpression (20,29,30). To address oncogene addiction in the context of MPN, we first assessed the effects of constitutive miR-125a overexpression in vivo to gauge the phenotypes of an inducible miR-125a model to be described later.…”
Section: Functional Genomics Screen Identified Mir-125 Family Mirnas Asmentioning
confidence: 99%
“…The expression levels varied depending on the methodologies used for expression and controls, but are generally up to 20-fold compared with normal BM. These malignancies include myelodysplastic syndrome involving the del (5q), 39,40 AMLs harboring the AML1/ETO translocation, 41 AMLs associated with the FLT3 mutation, 41 a few cases of chronic myelogenous leukemia, myeoproliferative neoplasms 42 and acute promyelocytic leukemia 43,44 (Table 1). The most investigated hematopoietic malignancy with increased expression of miR-125b is acute megakaryocytic leukemia associated with Down's syndrome (DS).…”
Section: Mir-125b In Myeloid Malignanciesmentioning
confidence: 99%